Navigating Power and Positionality in Ethnographic Spaces - Stewart, Tracey Mia (MUSICultures, 2025)
This article examines the influence of power and positionality in music research. I use key ethnographic moments of music making in Jamaican Maroon communities, the insights of a range of scholars, and my intersecting perspectives to investigate the following questions: How is access to cultural knowledge predicated on who we are, and who we are not? What does power sound like, and with whom and in what contexts does it reside? In what ways do histories of colonial domination and legacies of resistance reverberate through music and performance traditions, and how are those histories felt and heard in the present day?